The Development and Regulation of China's Insurance Market: History and Perspectives. Issue 2 (11th November 2013) - Chen, Bingzheng; Tennyson, Sharon; Wang, Maoqi; Zhou, Haizhen
Abstract China's private insurance market has been developing rapidly since the 1980s. Regulation of the market has developed in tandem with its growth. This article provides a systematic overview of China's insurance regulatory system and the evolving process of insurance supervision and regulation. The nature and direction of regulatory changes are evaluated in light of theories of public reform and the special character of China among developing economies.